((R)-(−)-3-Hydroxyquinuclidium)[FeCl4]; a plastic hybrid compound with chirality, ferroelectricity and long range magnetic ordering. Issue 13 (30th March 2021) - González-Izquierdo, Palmerina; Fabelo, Oscar; Cañadillas-Delgado, Laura; Beobide, Garikoitz; Vallcorba, Oriol; Salgado-Beceiro, Jorge; Sánchez-Andújar, Manuel; Martin, Carmen; Ruiz-Fuentes, Javier; García, José Eduardo; Fernández-Díaz, María Teresa; de Pedro, Imanol
Abstract : Scheme of the different phase transitions of (( R )-(−)-3-hydroxyquinuclidium)[FeCl4 ]. Abstract : Quinuclidinium salts and their derivatives are now in the focus of materials science as building units of multifunctional materials. Their properties can be easily switchable, allowing their use in a wide range of physical applications. One type of these kinds of materials, the homochiral hybrid halometallate ferroelectric compounds, is not well understood. In this work, ( R )-(−)-3-quinuclidinol hydrochloride was used in the synthesis of (( R )-(−)-3-hydroxyquinuclidium)[FeCl4 ]. The use of this enantiomeric cation forces crystallographic non-centrosymmetry, which was confirmed by polarimetry and circular dichroism spectroscopy. We studied the physical properties of this compound at different temperatures by single crystal, synchrotron and neutron powder X-ray diffraction, which showed a rich series of structural and magnetic phase transitions. From synchrotron powder X-ray diffraction data, a plastic phase was observed above 370 K (phase I). Between 370 K and ca. 310 K, an intermediate polar phase was detected, solved in a non-centrosymmetric polar space group ( C 2) (phase II). Below ca. 310 K, the compound crystallizes in the triclinic P 1 non-centrosymmetric space group (phase III) which is maintained down to 4 K, followed by phase IV, which shows tridimensional magnetic ordering. The temperature evolution of the neutron diffraction data shows the appearance of new reflections below 4 K. These reflections can be indexed to a commensurate propagation vector k = (0, 0, ½). The magnetic structure below T N was solved in the P s 1 Shubnikov space group, which gives rise to an antiferromagnetic structure, compatible with the magnetometry measurements. Near room temperature, the crystal phase transition is associated with a dielectric change. In particular, the phase transition between phase III (S.G.: P 1) and phase II (S.G.: C 2) involves an increase of symmetry between two non-centrosymmetric space groups. Therefore, it allows, by symmetry, the emergence of ferroelectric and ferroelastic ordering. Piezoresponse force microscopy (PFM) imaging measurements provided evidence for polarization switching and a local ferroelectric behavior of phase III at room temperature. Additionally, the obtained butterfly curve and hysteresis loop by PFM exhibits a low coercive voltage of ∼10 V. This value is remarkable, since it approaches those obtained for materials with application in ferroelectric random access memories (FeRAMs).